Cognitive resilience and psychological responses across a collegiate rowing season - Shields, M. R.; Brooks, M. A.; Koltyn, K. F.; Kim, J.-S.; Cook, D. B. (Medicine & Science in Sports & Exercise, 2017)
Introduction Student-athletes face numerous challenges across their competitive season. Although mood states have been previously studied, little is known about adaptations in other psychological responses, specifically cognition. The purpose of this study was to characterize cognitive function, mood, sleep, and stress responses at select time points of a season in collegiate rowers. It was hypothesized that during baseline, typical training, and recovery, athletes would show positive mental health profiles, in contrast to decreases in cognition with increases in negative mood and measurements of stress during peak training.